2021
DOI: 10.1037/npe0000148
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the pressure: The effect of monetary incentives on effort, emotions, and performance.

Abstract: Studies have shown that monetary incentives can trigger more effort but can end up hindering performance and that emotions affect performance. However, very few studies have empirically evaluated the incentive-performance relation by estimating the effect of a monetary reward on all three outcomes: effort, emotions, and performance. We estimate the effect of providing a monetary incentive on the cognitive effort, emotions, and performance of a group of university students while solving a mathematics and logica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Response time is a commonly used measure of exerted effort under pressure (e.g., Attali, 2016; Castro et al, 2018). The reaction times during maintenance periods of the OSPAN test trials—when participants held letters in mind while completing the true/false arithmetic calculations—were extracted and averaged as a measure of participants’ effort.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Response time is a commonly used measure of exerted effort under pressure (e.g., Attali, 2016; Castro et al, 2018). The reaction times during maintenance periods of the OSPAN test trials—when participants held letters in mind while completing the true/false arithmetic calculations—were extracted and averaged as a measure of participants’ effort.…”
Section: Methodsmentioning
confidence: 99%
“…Behaviorally, increased effort exertion often manifests as greater time-on-task (Bonner & Sprinkle, 2002). For example, adults completing mathematics problems for a financial reward maintained visual attention on key problem-solving areas to a greater extent than those performing without reward (Castro et al, 2018). Pressured participants also reattempted problems more frequently than controls (Castro et al, 2018).…”
Section: Uncertainty Arousal and Optimal Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Financial incentives are suggested to be an essential factor in student life. In some studies, it has been reported to enhance the academic performance of non-athlete students (Herranz-Zarzoso & Sabater-Grande, 2018), while others reported its negative effect on academic achievements (Castro, Yamada, Contreras, Linares, & Watson, 2021). Studies assessing the impact of financial-related variables on academic performance are incredibly scarce.…”
Section: Literature Reviewmentioning
confidence: 99%